Who Sits at the Table? A female farm activist's experience during the De Doorns farm workers strike, South Africa - Kara Grace Mackay (Universidade Federal do Norte do Tocantins, 2018)
This journal article tells the story of a female farm activist and a leader in the De Doorns 2012/2013 farm workers' strike. In this small agricultural town in the Western Cape, South Africa, workers downed tools, disrupting the harvest of export grapes for export table grapes and wine, and demanded a minimum wage of R150 per day. Ethnographic data - interviews, participant observation and archival documents - is used to document the female farm worker's journey into activism, her evolution and new consciousness of self through political work and participating in the strike. Rancière's (1999) theory of the "presumption of equality" is used to understand the gains made and losses incurred by the farm workers during and after the strike.